2005
DOI: 10.1021/jp051607a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Anisotropy Decay and Solvation Dynamics in a Nanocavity:  Coumarin 153 in Methyl β-Cyclodextrins

Abstract: Fluorescence anisotropy decay and solvation dynamics of coumarin 153 (C153) are studied in dimethyl beta-cyclodextrin (DIMEB) and trimethyl beta-cyclodextrin (TRIMEB) nanocavity in water. C153 binds to DIMEB and TRIMEB to form both 1:1 and 1:2 (C153:cyclodextrin) complexes. The anisotropy decays of C153 in DIMEB and TRIMEB are found to be biexponential. The fast component of anisotropy decay (approximately 1000 ps) is attributed to the 1:1 complex and the slower one (approximately 2500 ps) to the 1:2 complex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 71 publications
9
85
2
Order By: Relevance
“…The hydrodynamic diameter (2r h ) of 1:2 complex is roughly equal to the sum of height of two CD cavities. 13 Most recently, Roy et al observed an extremely slow anisotropy decay (time constant >20 ns) for the C153--cyclodextrin guest-host complex (Fig. 11).…”
Section: Fluorescence Anisotropy Decaymentioning
confidence: 93%
See 2 more Smart Citations
“…The hydrodynamic diameter (2r h ) of 1:2 complex is roughly equal to the sum of height of two CD cavities. 13 Most recently, Roy et al observed an extremely slow anisotropy decay (time constant >20 ns) for the C153--cyclodextrin guest-host complex (Fig. 11).…”
Section: Fluorescence Anisotropy Decaymentioning
confidence: 93%
“…Sen et al measured anisotropy decay of C153 inside di-and tri-methyl -CD. 13 They observed a bi-exponential decay with components 1000-1150 and 2500-2700 ps. They ascribed the components respectively to the 1:1 and 1:2 complex of C153 with cyclodextrin (Fig.…”
Section: Fluorescence Anisotropy Decaymentioning
confidence: 97%
See 1 more Smart Citation
“…CDs are well-known in their ability to form inclusion complexes with hydrophobic molecules in aqueous solution and a number of studies have been performed about photochemical properties of the CD complexes including fluorescent probes such as pyrene, anthracene, coumarin and their derivatives [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The number of species of inclusion complexes present in solution can be determined from fluorescence anisotropy decay. [9] The anisotropy decay profile of perylene in g-CD shows a single-exponential decay, which suggests that there is only one type of inclusion complexlikely to be the 1:2 complex (judging from the pH dependence of the fluorescence intensity). This fact is consistent with the behavior of a 1:2 complex previously reported.…”
mentioning
confidence: 99%